Nesfatin-1 Regulates Feeding, Glucosensing and Lipid Metabolism in Rainbow Trout - Blanco, Ayelén M.; Velasco, Cristina; Bertucci, Juan I.; Soengas, José L.; Unniappan, Suraj (Frontiers in Endocrinology, 2018)
Nesfatin-1 is an 82 amino acid peptide which has been involved in a wide variety of physiological functions in both mammals and fish. This study aimed to elucidate the role of nesfatin-1 on rainbow trout food intake, and its putative effects on glucose and fatty acid sensing systems. Intracerebroventricular administration of 25 ng/g nesfatin-1 resulted in a significant inhibition of appetite, likely mediated by the activation of central POMC and CART. Nesfatin-1 stimulated the glucosensing machinery (changes in sglt1, g6pase, gsase, and gnat3 mRNA expression) in the hindbrain and hypothalamus. Central fatty acid sensing mechanisms were unaltered by nesfatin-1, but this peptide altered the expression of mRNAs encoding factors regulating lipid metabolism (fat/cd36, acly, mcd, fas, lpl, pparα and pparγ), suggesting that nesfatin-1 promotes lipid accumulation in the neurons. In the liver, intracerebroventricular nesfatin-1 treatment resulted in decreased capacity for glucose use and lipogenesis and increased the potential of fatty acid oxidation. Altogether, the present results demonstrate that nesfatin-1 is involved in the homeostatic regulation of food intake and metabolism in fish.